Yorkshire Terrier - Killick, Robert (London Collins, 2003)
This guide is illustrated with step-by-step photoguides to training. It is divided into sections: you and your dog; breed characteristics and behaviour; caring for your dog; practical information on feeding, training, grooming, exercising; breeding, showing and healthcare and first aid
Include Color Illustration and Index
Keywords: Yorkshire terrier